NUTRITIONAL ASPECTS OF INFANT PARTICIPANTS IN A MOTHER-BABY PROGRAM: NUTRITIONAL ASPECTS OF INFANT PARTICIPANTS IN A MOTHER-BABY PROGRAM (Revista Contexto & Saúde, 2022)
In recent decades, exclusive breastfeeding (EBF) in Brazil has shown an upward trend, whose main gains were observed between 1986 and 2006, following a stabilization in 2013 that was 36.6%. The present study evaluated nutritional aspects of infants aged 0 to 6 months attended in the Mother-Baby Program. It is a quantitative and retrospective study. A database of mothers and infants treated in the Mother-Baby Program from March 2016 to June 2018 was used. Infants who received EBF and / or mixed until the sixth month of age were included. Birth weight classification and nutritional status classification were described using the weight growth curves for length (P / C) and length for age (C / I), as recommended by WHO. The sample consisted of 79 infants and 34.2% were exclusively breastfed. When correlating P / C with EBF duration, there was no significant difference, however, 26.6% of EBF children were classified as eutrophic when assessed P / C at 06 months of age, and 34.2% of EBF children up to 180 days. were of adequate length for age. When assessing P / C, we observed that 27.8% were born at risk for overweight and after 06 months of age were classified as obese. We can conclude from this study that exclusively breastfed children in the first semester of life had nutritional status of eutrophic, showing that breast milk is the ideal food for proper growth in the first six months of life.
Keywords: Breastfeeding; Nutritional status; Infants